Electroencephalographic correlates of continuous postural tasks of increasing difficulty - Edwards,A; Guven,O; Furman,M; Arshad,Q; Bronstein,A (Neuroscience, 2018)
Cortical involvement in postural control is well recognized, however the role of non-visual afferents remains unclear. Parietal cortical areas are strongly implicated in vestibulo-spatial functions, but topographical localization during balance tasks remains limited. Here, we use electroencephalography (EEG) during continuous balance tasks of increasing difficulty at single electrode positions. Twenty-four healthy, right-handed individuals performed four balance tasks of increasing difficulty (bipedal and unipedal) and a seated control condition with eyes closed. Subjective ratings of task difficulty were obtained. EEG was recorded from 32 electrodes; 5 overlying sensory and motor regions of interest (ROIs) were chosen for further investigation: C3, Cz, C4, P3, P4. Spectral power and coherence during balance tasks were analyzed in theta (4–8Hz) and alpha (8–12Hz) bands. Alpha power reduced as task difficulty increased and this reduction correlated with subjective difficulty ratings. Alpha coherence increased with task difficulty between C3–Cz–C4 electrode pairs. Differential changes in power were observed in Cz, suggestive of a distinct role at this electrode location, which captures lower limb cortical representation. Hemispheric asymmetry was observed, as reflected by greater reductions in theta and alpha power in right-sided areas. Our results demonstrate the functional importance of bilateral central and parietal cortices in continuous balance control. The hemispheric asymmetry observed implies that the non-dominant hemisphere is involved with online monitoring of postural control. Although the posterior parietal asymmetry found may relate to vestibular, somatosensory or multisensory feedback processing, we argue that the finding relates to active balance control rather than simple sensory-intake or reflex circuit activation.